2000
DOI: 10.1023/a:1008319923516
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic study of weekly gemcitabine and paclitaxel in chemo-naïve patients with advanced non-small-cell lung cancer

Abstract: The weekly administration of GEM and TAX is very well tolerated, and has shown promising antitumor activity in NSCLC. In view of the cumulative toxicity and of the pharmacokinetic profile of GEM, doses of 1500 mg/m2 of GEM and 100 mg/m2 of TAX are recommended for phase II studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…An IC 50 dose was not achieved in the NRP-1 transfected cells at this time point, even at supratherapeutic doses. The survival advantage was even more dramatic (Pp0.005) at 50 000 nM, a therapeutically relevant concentration within the range of the peak plasma levels achieved following bolus gemcitabine chemotherapy (De Pas et al, 2000;Fogli et al, 2002). At this dose, at least 30% more of the NRP-1-transfected cells survived compared to control cells.…”
Section: Effect Of Nrp-1 Overexpression On Susceptibility To Anoikismentioning
confidence: 92%
“…An IC 50 dose was not achieved in the NRP-1 transfected cells at this time point, even at supratherapeutic doses. The survival advantage was even more dramatic (Pp0.005) at 50 000 nM, a therapeutically relevant concentration within the range of the peak plasma levels achieved following bolus gemcitabine chemotherapy (De Pas et al, 2000;Fogli et al, 2002). At this dose, at least 30% more of the NRP-1-transfected cells survived compared to control cells.…”
Section: Effect Of Nrp-1 Overexpression On Susceptibility To Anoikismentioning
confidence: 92%
“…The worst nonhematological toxicity was grade 3 elevation in serum transaminases and grade 2 neurosensory toxicity in 8% and 5% of cycles, respectively. This study demonstrated that the weekly administration of paclitaxel and gemcitabine is well tolerated, and has promising antitumor activity in NSCLC at the recommended dose of 100 mg/m 2 paclitaxel and 1500 mg/m 2 gemcitabine (De Pas et al, 2000).…”
Section: Genetics and Drug Response In Non-small Cell Lung Cancermentioning
confidence: 70%
“…patients with stage III-IV NSCLC demonstrated objective responses at all dose levels, with an overall response rate of 43% in 30 evaluable patients (De Pas et al, 2000). Hematological toxicity included grade 4 neutropenia, grade 3 thrombocytopenia, and febrile neutropenia.…”
Section: Genetics and Drug Response In Non-small Cell Lung Cancermentioning
confidence: 99%
“…The interaction between paclitaxel and gemcitabine has extensively been studied [15][16][17][18]. Some investigators have reported no pharmacokinetic interactions between the two drugs.…”
Section: Introductionmentioning
confidence: 99%